2007
DOI: 10.1186/1471-2458-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and mental health in young adults: a longitudinal survey

Abstract: BackgroundAdverse childhood experiences (ACEs) have been consistently linked to psychiatric difficulties in children and adults. However, the long-term effects of ACEs on mental health during the early adult years have been understudied. In addition, many studies are methodologically limited by use of non-representative samples, and few studies have investigated gender and racial differences. The current study relates self-reported lifetime exposure to a range of ACEs in a community sample of high school senio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
441
8
18

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 742 publications
(536 citation statements)
references
References 48 publications
43
441
8
18
Order By: Relevance
“…These data are in agreement with several investigators reporting higher rates of anxiety disorders, depression, suicide ideation and attempts and self-harm behaviors among young adults and adults with childhood history of maltreatments. 57,64,65 Considering social functioning, subjects with CM reported a worse relationship with male peers during childhood and adolescence. These results seem to confirm previous studies, reporting an association between CM and a poor social functioning in early and middle childhood.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with several investigators reporting higher rates of anxiety disorders, depression, suicide ideation and attempts and self-harm behaviors among young adults and adults with childhood history of maltreatments. 57,64,65 Considering social functioning, subjects with CM reported a worse relationship with male peers during childhood and adolescence. These results seem to confirm previous studies, reporting an association between CM and a poor social functioning in early and middle childhood.…”
Section: Discussionmentioning
confidence: 99%
“…A recent longitudinal study has shown a very strong association between stressful life events in childhood and depressive symptoms and antisocial behavior in young adults [34]. In children, a significantly increased number of life events was reported prior to the onset of such mental health problems as mood disorders and depression [15,21,23,38], as well as enuresis, externalizing behavior, suicidal tendencies, and anorexia nervosa [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its detrimental impact on mental health (Kaufman, Plotsky et al 2000;Heim and Nemeroff 2001;Rutter 2002;Schilling, Aseltine et al 2007), psychosocial adversity also detrimentally impacts physical health (Flaherty, Thompson et al 2006;Heim, Wagner et al 2006;Sareen, Jacobi et al 2006). In addition, we and others have shown that patients with psychiatric difficulties have worse medical outcomes (Levine, Covino et al 1996;Katon 2003;Tarrier, Gregg et al 2005) and are at heightened risk for sustaining subsequent physical injuries (Rockwell, Dimsdale et al 1988;Swenson, Dimsdale et al 1991).…”
Section: Introductionmentioning
confidence: 99%